Cost‐efficacy of biologic therapies for psoriatic arthritis from the perspective of the Taiwanese healthcare system. (25th September 2015) - Yang, Tsong‐Shing; Chi, Ching‐Chi; Wang, Shu‐Hui; Lin, Jing‐Chi; Lin, Ko‐Ming
Abstract: Background: Biologic therapies are more effective but more costly than conventional therapies in treating psoriatic arthritis. Objectives: To evaluate the cost‐efficacy of etanercept, adalimumab and golimumab therapies in treating active psoriatic arthritis in a Taiwanese setting. Methods: We conducted a meta‐analysis of randomized placebo‐controlled trials to calculate the incremental efficacy of etanercept, adalimumab and golimumab, respectively, in achieving Psoriatic Arthritis Response Criteria (PsARC) and a 20% improvement in the American College of Rheumatology score (ACR20). The base, best, and worst case incremental cost‐effectiveness ratios (ICERs) for one subject to achieve PsARC and ACR20 were calculated. Results: The annual ICER per PsARC responder were US$27 047 (best scenario US$16 619; worst scenario US$31 350), US$39 339 (best scenario US$31 846; worst scenario US$53 501) and US$27 085 (best scenario US$22 716; worst scenario US$33 534) for etanercept, adalimumab and golimumab, respectively. The annual ICER per ACR20 responder were US$27 588 (best scenario US$20 900; worst scenario US$41 800), US$39 339 (best scenario US$25 236; worst scenario US$83 595) and US$33 534 (best scenario US$27 616; worst scenario US$44 013) for etanercept, adalimumab and golimumab, respectively. Conclusions: In a Taiwanese setting, etanercept had the lowest annual costs per PsARC and ACR20 responder, while adalimumab had the highest annual costs per PsARC and ACR responder.